Law Enforcement Against Criminal Acts of Drug Abuse in Correctional Institutions (Study at Semarang Class I Correctional Institution) - Raihan Adam Saputra; H Hartanto (Universitas Muhammadiyah Surakarta, 2023)
Drug abuse in correctional institutions is a serious challenge in law enforcement in Indonesia. This study aims to analyze the effectiveness of law enforcement against drug abuse crimes in Class I Semarang Correctional Institution. The research method used is field research with a qualitative approach. Data were obtained through in‐depth interviews with prison officers, inmates, and related law enforcement officials. In addition, direct observation was also conducted at the penitentiary to collect relevant data. The results showed that drug abuse within correctional institutions is a complex problem and requires a comprehensive approach. Factors contributing to drug abuse include lack of effective supervision, corrupt practices, and shortage of human resources and facilities. Law enforcement against drug abuse crimes inside correctional institutions still faces challenges, such as the low rate of case disclosure and difficulties in obtaining sufficient evidence.